(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
The health of the population is the most valuable benefit for the state, its economic and cultural development. It influences the level of mortality, total life expectancy, fertility, disability and, ultimately, determines the population [1].